2010
DOI: 10.3109/01421590903144110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a computer program (‘disect’) to consolidate anatomy knowledge: A randomised-controlled trial

Abstract: Background: The teaching of anatomy to medical undergraduates continues to develop. Medical imaging can accurately demonstrate anatomy. 'disect' is a computer program which manipulates and reconstructs real CT images in 3-D. Aim: To implement and assess a novel computer-based imaging resource. Methods: Third-year undergraduate medical students at the University of East Anglia were randomised to different methods of delivering the program -either self-directed use or guided use with worksheets. Knowledge of gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 13 publications
0
35
0
5
Order By: Relevance
“…Paired t ‐tests yielded a significant result on knowledge acquisition after 3DVT interventions ( P < 0.01). Two studies reported results on factual means from comparisons between 3DVT interventions; Tam et al () tested guided 3D CT images versus self‐learned 3D CT images and found no significant difference between the two interventions ( P = 0.52). Naaz () found no differences between sequential 2D‐3D and integrated 2D‐3D interventions on spatial means in teaching brain anatomy.…”
Section: Resultsmentioning
confidence: 99%
“…Paired t ‐tests yielded a significant result on knowledge acquisition after 3DVT interventions ( P < 0.01). Two studies reported results on factual means from comparisons between 3DVT interventions; Tam et al () tested guided 3D CT images versus self‐learned 3D CT images and found no significant difference between the two interventions ( P = 0.52). Naaz () found no differences between sequential 2D‐3D and integrated 2D‐3D interventions on spatial means in teaching brain anatomy.…”
Section: Resultsmentioning
confidence: 99%
“…53,54 I think that such technologies should be further explored, for it could be a valuable supplement wherever severe shortage in teaching gross anatomy exists. [55][56][57][58][59][60][61][62][63] In addition, some authors reported promising results Downloaded by [Selcuk Universitesi] at 06: 59 27 December 2014 using e-learning and computer-aided methods applied to anatomy teaching. [64][65][66][67] One of the actual challenges in anatomy teaching is in integrating traditional and modern methods in a modern curriculum rather than proving the superiority of one over the other or simply discarding the "old" ones.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…[14][15][16][17][18][19][20] E-learning allows the user to access the content virtually anywhere and at any time, as long as an internet connection is available. The package was also designed to allow the slowest of internet connections to support use, and is therefore compatible for use with any device that allows internet access and 'Flash' use.…”
Section: Technological Aspects Of Designmentioning
confidence: 99%